Farmland abandonment decreases the fire regulation capacity and the fire protection ecosystem service in mountain landscapes - Sil, Ângelo (2018)
This study explored and applied the concepts of Fire Regulation Capacity (FRC) and Fire Protection Ecosystem Service (FPES) in the assessment of the effects of landscape change in a mountain fire-prone landscape in Portugal. We adopted a modeling and simulation approach using BFOLDS-FRM with landscape data for years 1990 and 2006 (observed) and with three landscape scenarios for 2020. Proxy indicators for FRC (burned area and fire intensity) and for economic damage by fire (loss of provisioning ES) were used to establish trends in the supply and value of FPES. We found decreased FRC to restrain simulated fires burning over 100 ha from 1990 on and to regulate Very High and Extreme fire intensity levels, particularly under our 2020 scenario of Forest expansion. FPES is also expected to decrease, as indicated by higher fire-related damages, particularly if fuel hazard increases in the landscape. However, there were differences among scenarios, suggesting potential tradeoffs between FPES and the supply of provisioning ES. Planning and management in this and similar areas experiencing farmland abandonment must consider fire trends and patterns, since landscape change is a major driver affecting FRC and FPES, which may further be decreased by future climatic conditions.